コウタイイキ ジシン カンソクモウ (GLISN) ニヨル グリーンランド ヒョウショウ モニタリング - 豊国, 源知; トヨクニ, ゲンチ; 金尾, 政紀; カナオ, マサキ; 東野, 陽子; トウノ, ヨウコ; 姫野, 哲人; ヒメノ, テツト; 坪井, 誠司; ツボイ, セイジ; Childs, Dean; Anderson, Kent; et al. (2014)
P(論文) グリーンランド氷床は地球規模の気候変動に伴って融解が進行している.近年,氷床融解の過程で末端部の氷河が移動する際に,「氷河地震」と呼ばれる地震動が発生することが知られるようになり,地震観測による氷床モニタリングに関心が集まっている.2009 年に発足した「グリーンランド氷床の地震モニタリング観測網(GLISN)」は,氷床モニタリングを目的として国際共同でグリーンランドや周辺の島々に広帯域地震計を展開するプロジェクトである.日本はGLISN 発足時からの参加国として,2011 年から観測隊を派遣しており,米国と共同で氷床上に観測点1 点を新設したほか,他の観測点のメンテナンスにも従事している.これらの観測点から得られた長周期地震波形データは,全球地震波伝播モデリングによる理論波形との比較でチェックを行い,設置場所によるノイズの影響が少ない,良質なデータであることを確認した. Global climate change is currently causing melting of the Greenland ice sheet. Recently, a new type of seismic event, referred to as a "glacial earthquake", has been recognized. Such earthquakes are generated by the movements of large masses of ice within the terminal regions of glacier, and represent a new approach for monitoring ice sheet dynamics. In 2009, the multinational GreenLand Ice Sheet monitoring Network (GLISN), a large broadband seismological network in and around Greenland, was initiated to monitor these events. Japan, a partner country of the GLISN project, has been sending a field team to Greenland each year since 2011, when a joint USA and Japanese team first established a dual seismic-GPS station (station code: ICESG-GLS2) on the Greenland ice sheet. In 2012, the same team contributed to the maintenance of ICESG-GLS2, as well as two other stations (NUUK and DY2G-GLS1). The quality of the long-period seismic waveform data obtained by these stations has been checked by comparing the data with global synthetic seismograms. Results indicate that the data from the three stations have not been substantially affected by noise, and that the quality is well controlled. departmental bulletin paper